Chromonic liquid crystals: more questions than answers. Issue 2 (2nd April 2016) - Masters, Andrew
ABSTRACT: While much liquid crystal research is on either thermotropic liquid crystals or on lyotopic, surfactant systems, a fascinating third class of materials is that of chromonic liquid crystals. These systems show fascinating properties but are, as yet, poorly understood. This article reports a recent meeting in which the status of our current knowledge is reviewed.